Magnetic behavior of poly(3-methylthiophene): Metamagnetism and room-temperature weak ferromagnetism - Nascimentom, O. R.; De Oliveira, A. J A; Correa, A. A.; Bulhões, L. O S; Pereira, E. C.; Souza, V. M. [UNESP]; Walmsley, L. [UNESP] (American Physical Society (APS), 2003)
A weak ferromagnetic phase is shown in pressed pellets of partially doped poly(3-methylthiophene) (P3MT) in the whole range from 1.8 to 300 K in magnetic measurements. Thermoremanence data have been used to estimate the suppression of this phase to be around 815 K. We also show that instead of the classical antiferromagnetism for the first-order interaction that gives weak ferromagnetism as a second-order effect, metamagnetic behavior is observed. X-band electron spin resonance (ESR) measurements and magnetization measurements allowed us to estimate that 8.1% of the total number of spins contributes to the weak ferromagnetism at room temperature. The doping level obtained from the ESR data is in good agreement with that estimated from electron dispersive spectroscopy measurements.
Keywords: ferromagnetic material; poly(3 methylthiophene); polymer; unclassified drug; chemical model; conductor; electron spin resonance; magnetism; molecular interaction; room temperature; spectroscopy